2021
DOI: 10.1007/s11205-021-02654-2
|View full text |Cite
|
Sign up to set email alerts
|

Social Study Resources and Social Wellbeing Before and During the Intelligent COVID-19 Lockdown in The Netherlands

Abstract: The first intelligent COVID-19 lockdown resulted in radical changes within the tertiary educational system within the Netherlands. These changes posed new challenges for university students and many social welfare agencies have warned that it could have adverse effects on the social wellbeing (SWB) of university students. Students may lack the necessary social study-related resources (peer- and lecturer support) (SSR) necessary to aid them in coping with the new demands that the lockdown may bring. As such, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 69 publications
(101 reference statements)
3
30
0
Order By: Relevance
“…Both decreased [17] and unaltered academic performance [18] have been reported. With respect to student mental health, both a negative impact on mood, feelings of loneliness and the ability to concentrate [19], and no impact on mental health [20], have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Both decreased [17] and unaltered academic performance [18] have been reported. With respect to student mental health, both a negative impact on mood, feelings of loneliness and the ability to concentrate [19], and no impact on mental health [20], have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…As the COVID‐19 pandemic is an international phenomenon characterized by rapid changes and unknown progression (e.g., steady rise in case numbers, constant adaptions to governmental restrictions), individuals may particularly seek psychological security and stabilization. Feeling a sense of ‘we‐ness’ and knowing that people worldwide are going through the same stressful experience may provide such a secure environment during these turbulent times (Dovidio, Ikizer, Kunst, & Levy, 2020 ; Gloster et al, 2020 ; Van Zyl, 2021 ; van Zyl, Rothmann, & Zondervan‐Zwijnenburg, 2021 ). Through the feeling of being in this pandemic together, people may experience this low‐control situation as more controllable.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the different challenges associated with the current COVID-19 pandemic, university students are considered a population vulnerable to the onset of common mental health problems such as stress, depression and anxiety [4,5]. These could negatively affect their social interactions, motivation, concentration and study engagement [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several protective factors have been identified that enable the enhancement of student wellbeing, and buffer the effects of risk factors on student stress and psychological distress [26]. These protective factors are particularly effective during the current pandemic, with higher levels of social support (peer and teacher) being able to buffer against mental health issues [4,5]. Further buffering resources also include student characteristics such as emotional regulation and optimism [26,27].…”
Section: Introductionmentioning
confidence: 99%